Bilateral aneurysmal bone cyst of the mandible: A case report - Gopal HK Sharma; Ashok V Dabir; Deepa A Das; Preeti P Talreja-Kanchan (Wolters Kluwer Medknow Publications, 2015)
An aneurysmal bone cyst (ABC), usually considered a reactive lesion of bone rather than a cyst or true neoplasm, is believed to represent an exaggerated, localized, proliferative response of vascular tissue in bone. The case described here is of a 40-year-old female patient presenting with gradually increasing bilateral mandibular swelling of more than 1 year duration. The radiographic and cone beam computed tomography (CBCT) images showed bilateral, multilocular expansile radiolucent lesions in the mandible in the premolar-molar region. On considering the blood aspirate obtained and the histopathologic findings, the patient was diagnosed with bilateral aneurysmal bone cysts in the mandible, with probable pre-existing bone lesion.